Imaging rapidly deforming ocean island volcanoes in the western Galápagos archipelago, Ecuador. Issue 1 (21st January 2014) - Tepp, Gabrielle; Ebinger, Cynthia J.; Ruiz, Mario; Belachew, Manahloh
Abstract Using local body wave arrival‐time tomography methods to determine 3‐D seismic velocity structure, we imaged the plumbing system of Sierra Negra Volcano, Galápagos. This hot spot volcanic chain includes some of the fastest deforming volcanoes in the world, making this an ideal location to study shield volcano plumbing systems. We inverted P and S wave arrivals recorded on a 15‐station temporary array between July 2009 and June 2011 using an a priori 1‐D velocity model constrained by offshore refraction studies. With local seismicity from nearby volcanoes as well as the ring fault system, the model resolution is good between depths of 3 and 15.5 km. The propagation of S waves throughout this volume argues against any large high‐melt accumulations, although a shallow melt sill may exist above 5 km. We image a broad low‐velocity region (>25 km laterally) below Sierra Negra at depths ~8–15 km. No large, regional velocity increase is found within the limits of good resolution, suggesting that crust is thicker than 15 km beneath the western Galápagos archipelago. Our results are consistent with crustal accretion of mafic cumulates from a large‐volume magma chamber that may span the boundary between preplume and accreted crust. The similarity between our results and those of Hawaii leave open the possibility that the crust has also been thickened by under‐plating.